On Sequentially Defined Function Spaces and Bounded Linear Functionals - Supama (Talenta Publisher, 2021)
In this paper, we construct a sequentially defined function space L_p,q(Ω) and observe its topological properties. Further, we formulate necessary and sufficient conditions for bounded linear functionals on the space.